PANEL DATA LINEAR METHODS IN INVESTIGATING THE LONG-RUN PURCHASING POWER PARITY THEORY FOR A GROUP OF DEVELOPED COUNTRIES - CHOJI, NIRI MARTHA; AJAI, TERWASE P.; IHEDIOHA, SILAS A.; CHUN, PAMSON B. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The purchasing power parity (PPP) theory says that the nominal exchange rates between two nations ought to be equivalent to the ratio of the total price levels between the two countries. This study utilized the Pedroni test of cointegration to check if cointegration holds, further, the study used the dynamic ordinary least square (DOLS) and fully modified ordinary least square (FMOLS) in investigating the relationships between the nominal exchange rates and the domestic and foreign prices in order to say what that means for the countries involved. The paper found support for the PPP, and also, it was discovered that the domestic prices cause depreciation while the foreign prices cause appreciation on the nominal exchange rates. Consequently, depreciation of the nominal exchange rates will cause exports to be cheaper, imports more expensive and hence cause inflation to increase. Appreciation of the nominal exchange rates on the other hand will cause export to be more expensive, imports cheaper and hence reduce inflation in the 16 developed countries.